CHILD ABUSE IN THE NOVEL MATILDA BY ROALD DAHL:AN ANALYSIS OF POWER RELATION - Eva Nurul Fariha, - (2010)
ABSTRACT The research paper entitled "Child Abuse in the novel Matilda by Roald Dahl (an analysis of Power Relation) is aimed to identify the types of child abuse in the novel and how the main character reacts against adults' abusive acts toward her. The research is qualitative descriptive with the textual analysis approach. The analysis employs Power Relation approach. The result of analysis shows that child abuse is categorized into four types; verbal abuse, physical abuse, emotional or psychological abuse, and neglect. In addition, there are three ways the main character reacts toward adults' abusive acts; verbal resistance, physical resistance, and emotional or psychological resistance. The research portrays that family and school are two institutions where abusive acts toward children can happen.